An Online Respiratory Quotient-Feedback Strategy of Feeding Yeast Extract for Efficient Arachidonic Acid Production by Mortierella alpina - Li, Xiangyu; Yu, Chao; Yao, Jianming; Wang, Zhiming; Lu, Shuhuan (Frontiers in Bioengineering and Biotechnology, 2018)
Mortierella alpina (M. alpina) is well known for arachidonic acid (ARA) production. However, low efficiency and unstableness are long existed problems for industrial production of ARA by M. alpina due to the lack of online regulations. The aim of the present work is to develop an online-regulation strategy for efficient and stable ARA production in industry. The strategy was developed in 50 L fermenters and then applied in a 200 m3 fermenter. Results indicated that yeast extract (YE) highly increased cell growth in shake flask, it was then used in bioreactor fermentation by various feeding strategies. Feeding YE to control respiratory quotient (RQ) at 1.1 during 0~48 h and at 1.5 during 48~160 h, DCW and ARA titre reached 53.1 and 11.49 g/L in 50 L fermenter, which were increased by 79.4% and 36.9% as compared to that without YE feeding, respectively. Then the online RQ-feedback strategy was applied in 200 m3 bioreactor fermentation and an average ARA titre of 16.82 g/L was obtained from 12 batches, which was 41.0% higher than the control batches. This is the first report on successful application of online RQ-feedback control of YE in ARA production, especially in an industrial scale of 200 m3 fermentation. It could be applied to other industrial production of microbial oil by oleaginous microorganisms.